The ambiguity of human ashes: Exploring encounters with cremated remains in the Netherlands. Issue 1 (2nd January 2017) - Mathijssen, Brenda
ABSTRACT: This article explores cremation and disposal practices in the Netherlands, focusing on the attitudes and experiences of bereaved Dutch people in relation to cremated remains. In academic and professional narratives, human ashes are commonly described as "important, " as "sacred, " and as a vehicle to continue intense and physical relationships with the dead. Based on quantitative and qualitative data this article illustrates the ambiguity of such relationships. It highlights the diverse experiences, unexpected challenges, and moral obligations that can be evoked by the deceased's ashes, where the latter are seen as embedded in material practices and entangled in social relationships.